The theory of mental spaces in Arabic cognitive linguistic research between theory and application. - SAOUDI, Djahida; Kbaili, abdelghani (Milev Journal of Research and Studies, 2022)
The continuous development of linguistics has produced many branches of science, most recently cognitive linguistics with the theories based on it for studying semantics and syntax. Accordingly, this article deals with the theory of mental spaces (MS) from an applied and theoretical Arabic perspective. As one of the theories of cognitive linguistics, the purpose of this research is to determine the value of MS theory in Arabic research through the field of cognitive linguistics. Knowing the nature of the Arab reception of this theory is based on the following questions: what is MS theory and its procedures? What is the Arabic perception of MS theory in Arabic linguistic research? What is the nature of the Arabic application of MS theory? The answer to these questions required a descriptive approach to determining the status of Arab reception of MS theory, and the most important result was that the theory of MS did not receive sufficient and comprehensive Arab linguistic study of all its issues.